2019
DOI: 10.3390/ijms20030629
|View full text |Cite
|
Sign up to set email alerts
|

Diuretic Effects of Sodium Glucose Cotransporter 2 Inhibitors and Their Influence on the Renin-Angiotensin System

Abstract: The renin-angiotensin system (RAS) plays an important role in regulating body fluids and blood pressure. However, inappropriate activation of the RAS contributes to the pathogenesis of cardiovascular and renal diseases. Recently, sodium glucose cotransporter 2 (SGLT2) inhibitors have been used as anti-diabetic agents. SGLT2 inhibitors induce glycosuria and improve hyperglycemia by inhibiting urinary reabsorption of glucose. However, in the early stages of treatment, these inhibitors frequently cause polyuria a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

8
79
1
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 129 publications
(100 citation statements)
references
References 93 publications
(105 reference statements)
8
79
1
1
Order By: Relevance
“…In our study, despite preexisting medication with RAAS inhibitors in nearly all patients, changes of fluid status were accompanied by a trend towards elevated plasma renin activity and serum aldosterone concentration after 30 days, suggesting an increased activity of RAAS, with normalization after 6 months. Our results therefore confirm active counteracting mechanisms of fluid regulation after inhibition of SGLT2 as discussed previously [39].…”
Section: Discussionsupporting
confidence: 91%
See 2 more Smart Citations
“…In our study, despite preexisting medication with RAAS inhibitors in nearly all patients, changes of fluid status were accompanied by a trend towards elevated plasma renin activity and serum aldosterone concentration after 30 days, suggesting an increased activity of RAAS, with normalization after 6 months. Our results therefore confirm active counteracting mechanisms of fluid regulation after inhibition of SGLT2 as discussed previously [39].…”
Section: Discussionsupporting
confidence: 91%
“…In accordance to our finding of transient decreased OH and ECW, increase of urine volume after initiation of SGLT2 inhibitors has also been found to be transient and was caused rather by natriuresis than by osmotic diuresis due to glycosuria [29,38]. After initiation of SGLT2 inhibition, an initial, but no long-term elevated natriuresis has been shown, and compensatory mechanisms such as increased sodium reuptake through following tubular transporters and activation of RAAS, have been investigated [38,39]. Systemic RAAS has been shown to be activated transiently in patients with type 2 diabetes after beginning of SGLT2 inhibitors [39], whereas intrarenal RAAS is not activated after SGLT2 inhibition [40].…”
Section: Discussionsupporting
confidence: 82%
See 1 more Smart Citation
“…One explanation for the absence of this anticipated adverse event is that the diuresis and polyuria caused by SGLT2 inhibitors could act counter to the expected glucose growth rate enhancement, whereby the increased flow through the urinary tract (with associated increased voiding) reduces urine bacterial loads and/or prevents successful ascension of pathogenic bacteria. On average, the daily urine volume increases by about 1.6‐fold compared with before the medication was started; although this varies by SGLT2 inhibitor use and patient population . The idea that increased urinary flow could play a role is supported by a recent large randomized trial of increased fluid consumption in patients at high risk for UTI, which showed that increased water intake doubled urinary volume and reduced UTIs by approximately 50% over a 12‐month period …”
Section: An Overview Of Recent Literature Assessing the Risk Of Uti Wmentioning
confidence: 99%
“…Recent studies suggest that the increased urine volume caused by SGLT2 inhibitors does attenuate over time . For some studies, the attenuation occurs over a number of days, while in other studies the increased urine volume persists up to 12 weeks after starting an SGLT2 inhibitor . This attenuation over time may explain why some clinical trials of SGLT2 inhibitors with a longer duration of follow‐up did detect an increased risk of UTI with SGLT2 inhibitors.…”
Section: An Overview Of Recent Literature Assessing the Risk Of Uti Wmentioning
confidence: 99%